Narrator profile in translation: Work-in-progress for a semiautomatic analysis of narratorial dialogistic and attitudinal positioning in translated fiction - Assis Rosa, Alexandra (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper presents work-in-progress for the development of a semi-automatic methodology for the analysis of shifts in narrator profile in translated fiction. Such a methodology is developed for a comparative quantitative analysis of electronic source and target texts organized in a parallel corpus. The first and main part of this paper presents the theoreti-cal motivation for the organization of two systems of categories focusing on the relationship between the two discursive centres involved in reported speech - narrator and character (but also quoter and quotee in other text types) - by developing the proposals of dialogistic/intertextual and attitu-dinal positioning in Appraisal Theory. The second part of this paper ana-lyses a selection of examples illustrative of such cate gories, and presents and comments the results of the comparative quantitative analysis of Charles Dickens's Oliver Twist and eight European Portuguese translations for juvenile and adult readerships. This comparative analysis proves the methodology operative and shows evidence of two tendencies: ‘levelling-out’ and ‘explicitation’, which, although elsewhere identified as trans-lational universals, may here be identified as norms because they correlate with the independent variable target readership. The purpose of developing this methodology is to help describe the way interlingual translation may transform narrator profile as well as contribute to the formulation of trans-lational norms.